(untitled) (Archives of Clinical Psychiatry, 2019)
Background: Substance use and smoking exert devastating impact on sleep, especially hindering the ease of falling asleep, compromising the sleep maintenance, and distorting the sleep cycles. PERIOD genes are believed to play a role in individual differences in sleep timing by influencing circadian. Objective: The aim of this study was to ascertain whether Per3 VNTR variant affects suspectibility of individuals to substance use disorder (SUD) and smoking status in a Turkish population. Methods: A total of 549 subjects, including 212 SUD patients, 160 smoker, and 177 healthy controls, matched by ethnicity, age, and gender, were recruited in a case-control study. Genotyping of Per3 variant was performed using PCR method. Results: When the SUD, smoker groups and controls were compared in terms of 5R/5R, 5R/4R, 4R/4R genotypes, no significant difference was observed. Besides, allele frequencies of Per3 VNTR were similar among the groups. Discussion: Our data indicate that Per3 VNTR variant is not associated with the risk of SUD and smoking status in our population.